Hyperpolarizing Concentrated Metronidazole 15NO2 Group over Six Chemical Bonds with More than 15 % Polarization and a 20 Minute Lifetime. Issue 37 (30th May 2019) - Shchepin, Roman V.; Birchall, Jonathan R.; Chukanov, Nikita V.; Kovtunov, Kirill V.; Koptyug, Igor V.; Theis, Thomas; Warren, Warren S.; Gelovani, Juri G.; Goodson, Boyd M.; Shokouhi, Sepideh; Rosen, Matthew S.; Yen, Yi‐Fen; et al.
Abstract: The NMR hyperpolarization of uniformly 15 N‐labeled [ 15 N3 ]metronidazole is demonstrated by using SABRE‐SHEATH. In this antibiotic, the 15 NO2 group is hyperpolarized through spin relays created by 15 N spins in [ 15 N3 ]metronidazole, and the polarization is transferred from parahydrogen‐derived hydrides over six chemical bonds. In less than a minute of parahydrogen bubbling at approximately 0.4 μT, a high level of nuclear spin polarization ( P 15N ) of around 16 % is achieved on all three 15 N sites. This product of 15 N polarization and concentration of 15 N spins is around six‐fold better than any previous value determined for 15 N SABRE‐derived hyperpolarization. At 1.4 T, the hyperpolarized state persists for tens of minutes (relaxation time, T 1 ≈10 min). A novel synthesis of uniformly 15 N‐enriched metronidazole is reported with a yield of 15 %. This approach can potentially be used for synthesis of a wide variety of in vivo metabolic probes with potential uses ranging from hypoxia sensing to theranostic imaging. Abstract : Spinning tops it ! The 15 NO2 group of [ 15 N3 ]metronidazole can be efficiently hyperpolarized ( P 15N ≈16 %) by 15 N SABRE‐SHEATH through spin relays created by the network of 15 N spins within the molecule, the hyperpolarization being transferred from parahydrogen‐derived iridium hydrides over up to six chemical bonds. All three 15 N sites of [ 15 N3 ]metronidazole are hyperpolarized in about 1 minute at concentrations up to 41 mm (see figure).